Framing Analysis of Village Funding Corruption in Media Suaramerdeka.Com in Central Java, Indonesia, 2019 - Triyono, Agus (International Journal of Criminology and Sociology, 2022)
Various corruption cases have occurred in many villages in Central Java, Indonesia. Corruption is mostly carried out by village officials in running the government. One of many factors causing such corruption cases is the existence of village fund assistance. These corruption cases have been published in the mass media, Specifically on online media, i.e. suaramerdeka.com This study aims to look at the media framing of corruption cases that have occurred in Central Java, particularly concerning village funding assistance in various regions through the online media suaramerdeka.com. This study is a constructive paradigm research. The approach method used is qualitative. Meanwhile, the analytical method used is the Robert N. Entman framing analysis model. The findings of this study stated that suaramerdeka.com framed the perpetrators of corruption as village officials. Although it is acknowledged that not all of them are corrupt, the news seems to give the impression that village officials have conducted a lot of corruption. However, on the other hand, the news content of suaramerdeka.com as a local media in Central Java also lacks detail in reporting corruption issues. Moreover, it seems only normative and does not show that it is a strong media in covering corruption cases. The explanation of the news was not very in-depth.